An N‐Heterocyclic Boryloxy Ligand Isoelectronic with N‐Heterocyclic Imines: Access to an Acyclic Dioxysilylene and its Heavier Congeners. Issue 15 (14th February 2019) - Loh, Ying Kai; Ying, Lu; Ángeles Fuentes, M.; Do, Dinh Cao Huan; Aldridge, Simon
Abstract: Introduced here is a new type of strongly donating N‐heterocyclic boryloxy (NHBO) ligand, [(HCDippN)2 BO] − (Dipp=2, 6‐diisopropylphenyl), which is isoelectronic with the well‐known N‐heterocyclic iminato (NHI) donor class. This 1, 3, 2‐diazaborole functionalized oxy ligand has been used to stabilize the first acyclic two‐coordinate dioxysilylene and its Ge, Sn, and Pb congeners, thereby presenting the first complete series of heavier group 14 dioxycarbene analogues. All four compounds have been characterized by X‐ray crystallography and density‐functional theory, enabling analysis of periodic trends: the potential for the [(HCDippN)2 BO] − ligand to subtly vary its electronic‐donor capabilities is revealed by snapshots showing the gradual evolution of arene π coordination on going from Si to Pb. Abstract : New O‐donor ligand : By exploiting the isoelectronic relationship with N‐heterocyclic imines (NHIs), a new class of N‐heterocyclic boryloxy (NHBO) ligand, which is a strong O‐donor, is introduced. The NHBO ligand is used to generate the first acyclic two‐coordinate dioxysilylene and its heavier (Ge, Sn, Pb) congeners, which represent the first complete series of heavier group 14 dioxycarbene analogues.